PENGEMBANGAN LKPD BERBASIS CONTEXTUAL TEACHING LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Hariyati, Dwi Srirejeki; Yulianti, Yulianti; Sulistyowati, Prihatin (Universitas Islam Darul 'Ulum Lamongan, 2024)
Teaching materials are an important component used by teachers in the learning process. With teaching materials combined with daily activities, it can help teachers easily achieve learning goals for students. One of these teaching materials is the LKPD (Student Worksheet) teaching material. The purpose of this study is to develop LKPD based on Contextual Teaching Learning in Class IV Elementary School Cooperative Lifestyle Learning and to determine the feasibility, practicality, and effectiveness of the LKPD. This type of research is a type of research and development or commonly called Research and Development (R&D). In this study, product development was carried out using a 4-D model development design developed by Thiagarajan with the stages of Define, Design, Development and Dissemination. Based on the results of this study, it shows that LKPD can increase learning interest and good learning outcomes. It can be concluded that the LKPD teaching materials based on Contextual Teaching Learning are valid, practical, and effective for use by grade V elementary school students.